A novel mutation in STK11 gene is associated with Peutz-Jeghers Syndrome in Indian patients - Singh Lalji; Mohankrishna P; Rao G; Reddy D; Thakur Nikita; Chandak Giriraj R (BMC, 2006)
Abstract Background Peutz-Jeghers syndrome (PJS) is a rare multi-organ cancer syndrome and understanding its genetic basis may help comprehend the molecular mechanism of familial cancer. A number of germ line mutations in the STK11 gene, encoding a serine threonine kinase have been reported in these patients. However, STK11 mutations do not explain all PJS cases. An earlier study reported absence of STK11 mutations in two Indian families and suggested another potential locus on 19q13.4 in one of them. Methods We sequenced the promoter and the coding region including the splice-site junctions of the STK11 gene in 16 affected members from ten well-characterized Indian PJS families with a positive family history. Results We did not observe any of the reported mutations in the STK11 gene in the index patients from these families. We identified a novel pathogenic mutation (c.790_793 delTTTG) in the STK11 gene in one index patient (10%) and three members of his family. The mutation resulted in a frame-shift leading to premature termination of the STK11 protein at 286th codon, disruption of kinase domain and complete loss of C-terminal regulatory domain. Based on these results, we could offer predictive genetic testing, prenatal diagnosis and genetic counselling to other members of the family. Conclusion Ours is the first study reporting the presence of STK11 mutation in Indian PJS patients. It also suggests that reported mutations in the STK11 gene are not responsible for the disease and novel mutations also do not account for many Indian PJS patients. Large-scale genomic deletions in the STK11 gene or another locus may be associated with the PJS phenotype in India and are worth future investigation.